Automatic Music Summarization. A “Thumbnail” Approach - GŁACZYNSKI, Jakub; ŁUKASIK, Ewa (Archives of Acoustics, 2011)
In the paper, various approaches to automatic music audio summarization are discussed. The project described in detail, is the realization of a method for extracting a music thumbnail – a fragment of continuous music of a given duration time that is most similar to the entire music piece. The results of subjective assessment of the thumbnail choice are presented, where four parameters have been taken into account: clarity (representation of the essence of the piece of music), conciseness (the motifs are not repeated in the summary), coherence of music structure, and overall quality of summary usefulness.